Macroscopic optical physiological parameters correlate with microscopic proliferation and vessel area breast cancer signatures. Issue 1 (December 2015) - Chung, So; Feldman, Michael; Martinez, Daniel; Kim, Helen; Putt, Mary; Busch, David; Tchou, Julia; Czerniecki, Brian; Schnall, Mitchell; Rosen, Mark; DeMichele, Angela; Yodh, Arjun; et al.
Abstract Introduction Non-invasive diffuse optical tomography (DOT) and diffuse correlation spectroscopy (DCS) can detect and characterize breast cancer and predict tumor responses to neoadjuvant chemotherapy, even in patients with radiographically dense breasts. However, the relationship between measured optical parameters and pathological biomarker information needs to be further studied to connect information from optics to traditional clinical cancer biology. Thus we investigate how optically measured physiological parameters in malignant tumors such as oxy-, deoxy-hemoglobin concentration, tissue blood oxygenation, and metabolic rate of oxygen correlate with microscopic histopathological biomarkers from the same malignant tumors, e.g., Ki67 proliferation markers, CD34 stained vasculature markers and nuclear morphology. Methods In this pilot study, we investigate correlations of macroscopic physiological parameters of malignant tumors measured by diffuse optical technologies with microscopic histopathological biomarkers of the same tumors, i.e., the Ki67 proliferation marker, the CD34 stained vascular properties marker, and nuclear morphology. Results The tumor-to-normal relative ratio of Ki67-positive nuclei is positively correlated with DOT-measured relative tissue blood oxygen saturation (R = 0.89, p -value: 0.001), and lower tumor-to-normal deoxy-hemoglobin concentration is associated with higher expression level of Ki67 nuclei (p -value: 0.01). In a subset of the Ki67-negative group (defined by the 15 % threshold), an inverse correlation between Ki67 expression level and mammary metabolic rate of oxygen was observed (R = −0.95, p -value: 0.014). Further, CD34 stained mean-vessel-area in tumor is positively correlated with tumor-to-normal total-hemoglobin and oxy-hemoglobin concentration. Finally, we find that cell nuclei tend to have more elongated shapes in less oxygenated DOT-measured environments. Conclusions Collectively, the pilot data are consistent with the notion that increased blood is supplied to breast cancers, and it also suggests that less conversion of oxy- to deoxy-hemoglobin occurs in more proliferative cancers. Overall, the observations corroborate expectations that macroscopic measurements of breast cancer physiology using DOT and DCS can reveal microscopic pathological properties of breast cancer and hold potential to complement pathological biomarker information.